Public finance and public policy - Gruber, Jonathan (New York, 2013)
Jonathan Gruber's groundbreaking Public Finance and Public Policy was the first textbook to truly reflect the way public policy is created, implemented, and researched. Like no other text available, it integrated real-world empirical work and coverage of transfer programs and social insurance into the traditional topics of public finance. From its first edition, the book quickly became the market-leading text for Public Finance and Public Policy courses, and the margin is growing. Thoroughly updated, this timely new edition gives students the basic tools they need to understand the driving issues of public policy today, including healthcare, education, global climate change, entitlements, and more.
Keywords: Public finance